Factibilidad de la implementación de la filosofía lean en el sector público en la gestión de operaciones de la EP-EMAPAR. - Muñoz Rubio, Nelson Patricio (2025)
Efficient operations management is fundamental to ensuring productivity and quality in organizations. The need and importance of this topic lie in the pursuit of operational efficiency, customer satisfaction, and the exploration of a quality service for EP-EMAPAR users. In this context, the application of Lean philosophy in the public sector can be an effective strategy for the main objective of this research, which is to reach the acceptance of the feasibility of implementing the Lean philosophy in the company and the services it provides to citizens, optimizing processes because it provides a way to improve operations using the least possible resources: human effort, fewer equipment, less time, less materials, and less space, continually approaching the customer's desires. The research methodology employs a quantitative approach, collecting and analyzing data. The main expected results are the following: to know what openness exists for implementing new ways of thinking about processes in operations management; and with this, finally, to propose strategies and tools that are applicable to the reality of EP-EMAPAR, with the aim of improving the efficiency of water and sewerage services.